2008
DOI: 10.1177/1359105308095966
|View full text |Cite
|
Sign up to set email alerts
|

Passage Meditation Improves Caregiving Self-efficacy among Health Professionals

Abstract: Relational caregiving skills remain seldom studied in health professionals. We evaluated effects on health professional relational caregiving self-efficacy from an eight-week, 16-hour training in self-management tools. Physicians, nurses, chaplains, and other health professionals were randomized after pretest to treatment (n = 30) or waiting list (n = 31). Training used a previously researched program of Easwaran (1991/1978) derived from spiritual wisdom traditions. Changes were measured using a 34-item caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 26 publications
1
40
1
7
Order By: Relevance
“…The results of this study, combined with other self-efficacy research, suggest the potential for interventions that directly enhance self-efficacy thereby increasing caregivers' positive experiences in the caregiving role. Caregiver self-efficacy is known to be enhanced through a variety of techniques including: (a) relaxation training (Fisher & Laschinger, 2001), (b) meditation and yoga (Oman, Richards, Hedberg, & Thoresen, 2008), (c) home-based intervention (Gitlin, Beauchamp, Irvine, Seeley, and Johnson (2005) found that dementia caregiver self-efficacy and experienced positive aspects of caregiving both increased following caregiver participation in an online multi-component intervention program. Although they did not postulate a mechanism for this finding, one may speculate whether selfefficacy was enhanced through the multi-component intervention and if this, in turn, increased caregivers' ability to identify positive aspects of caregiving.…”
Section: Aging and Mental Health 685mentioning
confidence: 99%
“…The results of this study, combined with other self-efficacy research, suggest the potential for interventions that directly enhance self-efficacy thereby increasing caregivers' positive experiences in the caregiving role. Caregiver self-efficacy is known to be enhanced through a variety of techniques including: (a) relaxation training (Fisher & Laschinger, 2001), (b) meditation and yoga (Oman, Richards, Hedberg, & Thoresen, 2008), (c) home-based intervention (Gitlin, Beauchamp, Irvine, Seeley, and Johnson (2005) found that dementia caregiver self-efficacy and experienced positive aspects of caregiving both increased following caregiver participation in an online multi-component intervention program. Although they did not postulate a mechanism for this finding, one may speculate whether selfefficacy was enhanced through the multi-component intervention and if this, in turn, increased caregivers' ability to identify positive aspects of caregiving.…”
Section: Aging and Mental Health 685mentioning
confidence: 99%
“…Potential mediators and moderators are analysed, including adherence to programme practices, stress reduction, and increased access to spiritual resources. Compassionate love gains are also analysed as possible mediators of previously reported increases in caregiving self-efficacy (Oman, Richards, Hedberg, & Thoresen, 2008). We close by discussing implications and further directions.…”
Section: Introductionmentioning
confidence: 96%
“…Cholewa and Irwin (2008) concluded on the basis of their evidence that the interventions were effective, and have recommended wider-spread implementation and evaluation. A second study using eight techniques is discussed below (Oman, Richards, Hedberg, & Thoresen, 2008).…”
Section: Observing Other Symptomsmentioning
confidence: 99%
“…The study described next used a combination of eight techniques or 'points'. Oman et al (2008) conducted a randomized trial and qualitative assessment of passage meditation on the relational care-giving self-efficacy in a group of experienced health professionals (physicians, nurses, chaplains and others). The authors examined the impact of an eight-week, 16-hour training toolkit on relational care-giving self-efficacy.…”
Section: Domain 9 Faith-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation